2022
DOI: 10.5194/nhess-22-4039-2022
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of air quality impacts from individual forest fires in New South Wales, Australia

Abstract: Abstract. Wildfires and hazard reduction burns produce smoke that contains pollutants including particulate matter. Particulate matter less than 2.5 µm in diameter (PM2.5) is harmful to human health, potentially causing cardiovascular and respiratory issues that can lead to premature deaths. PM2.5 levels depend on environmental conditions, fire behaviour and smoke dispersal patterns. Fire management agencies need to understand and predict PM2.5 levels associated with a particular fire so that pollution warning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previous research has aimed to understand differences in smoke production, transport and exposure by fire type. However, fire type has not consistently been a useful or the best available predictor of air-quality-related factors, including fuel consumption [11], PM 2.5 concentration from individual fires [15] and large particle plume top height [13], with fire area usually a more reliable predictor. Some studies have found large differences in the effect of wildfire and HRB fire area on air quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has aimed to understand differences in smoke production, transport and exposure by fire type. However, fire type has not consistently been a useful or the best available predictor of air-quality-related factors, including fuel consumption [11], PM 2.5 concentration from individual fires [15] and large particle plume top height [13], with fire area usually a more reliable predictor. Some studies have found large differences in the effect of wildfire and HRB fire area on air quality.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme end of fire behaviour distributions (largest areas, fastest spreading fires) are wildfires, but these are a minority of all fires. The outcome of this is that other fire characteristics (intensity, fuel amount, weather) that directly influence smoke production, transport and exposure are probably better than fire type for the prediction of air quality metrics [15]. Distance from a fire is also important for understanding PM 2.5 levels, with monitoring stations close to fires (<20 km) having higher PM 2.5 levels than those farther away [15,33], and HRBs (and their plumes) tend to be closer to urban areas where monitors are than wildfires [14,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation